Analisis Perilaku Narsisme pada Siswa Kelas XII MIPA SMA Negeri 1 Tahun 2024 - Pratiwi, Rani Diah (Universitas Tanjungpura, 2024)
Narcissism is an attitude that excessively involves oneself to the extent of neglecting the needs of those around them. Additionally, it is characterized by a sense of being more capable, unique, and special compared to others. In psychology, the term narcissism can be classified as a personality disorder. The primary issue addressed in this research is: How is the analysis of narcissistic behavior among the twelfth-grade science students at SMA Negeri 1 Sintang in 2024? The sub-issues are: (1) What are the characteristics of narcissistic behavior among the twelfth-grade science students at SMA Negeri 1 Sintang in 2024? (2) What factors contribute to narcissistic behavior among these students? (3) What efforts do guidance and counseling teachers undertake to help address narcissistic behavior among the twelfth-grade science students at SMA Negeri 1 Sintang in 2024? The method employed in this study is descriptive. The population for this research is the analysis of narcissistic behavior among the twelfth-grade science students at SMA Negeri 1 Sintang in 2024. This study utilizes a quantitative approach. Data collection techniques involve indirect communication, and the data collection instrument used is a questionnaire. Data analysis is conducted using percentage formulas. The results indicate that the analysis of narcissistic behavior among the twelfth-grade science students at SMA Negeri 1 Sintang is categorized as